The sense of belonging reduces ingroup favoritism in children - Park, Joo Hyang; Jin, Kyong-sun (Frontiers in Psychology, 2022)
Belonging is an important motive for intergroup behavior. Adults display pronounced ingroup favoritism when the sense of inclusion by an ingroup is decreased or threatened. The present study investigated whether ingroup belonging reduces ingroup favoritism in 6-year-old children in terms of costly sharing. Children were allocated to a novel group in a minimal-group paradigm. In two conditions, children played a brief ball-tossing game and were either included (ingroup-inclusion condition) or excluded (ingroup-exclusion condition) by their ingroup members. Children in a no-interaction condition did not have any interactions with the members of the ingroup. After this manipulation, we tested the extent to which children shared resources with ingroup and outgroup members. We found that children in the ingroup-exclusion and no-interaction conditions shared more resources with their ingroup member than their outgroup member, while children in the ingroup-inclusion condition shared equally with the ingroup and outgroup members. These results could inform interventions aimed at fostering positive intergroup relations.